Henry Hobbs Space Voyager. - "Cave, Kathryn" (Hodder Children's: London, 2001)
Stowing away on the spaceship to escape his horrible brother seemed like a good idea until Henry discovers the voyage is going to take 50 years! Somehow Henry has to escape. But how?
Keywords: Science fiction